ANALISIS PEMBELAJARAN DENGAN KURIKULUM 2013 DAN KURIKULUM MERDEKA DALAM PERSPEKTIF GURU SD - Fatoni, Rahmad Kaosar; Sartika, Septi Budi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research will analyze the of the 2013 Curriculum and the Merdeka Curriculum at SDN Sidokare 2 Sidoarjo by focusing on the teacher's perspective. As well as describing the various challenges experienced in implementing the 2013 Curriculum and Merdeka Curriculum. This research is a qualitative descriptive research, namely research about individuals, groups, and one organization at a certain time. Data collection techniques in this research are (1) observation, (2) documentation, and (3) interviews. Data validation in research is source triangulation. The data analysis technique in this research is an interactive model. Interactive model data analysis, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions or verification. The research results show that: Teachers have carried out assessments based on the 2013 curriculum and teachers have also implemented various methods in learning activities to create an active, creative and fun learning atmosphere. Teachers' perceptions are positive and appreciative of the implementation of the Merdeka Curriculum in primary schools. Teachers have a crucial role in the development and implementation of the curriculum in primary schools. The effectiveness of curriculum implementation largely relies on the level of dedication and intensity shown by the teacher in the classroom.